ERODIBILITAS TANAH (K) DI SEPANJANG JALUR JALAN MANADO-TOMOHON SOIL ERODIBILITY (K) ALONG THE ROAD MANADO-TOMOHON - Michiko A. Lengkong; Tommy Sondakh; Yani E.B. Kamagi; Maria Montolalu (COCOS, 2015)
Abstract The objective of this study aims to determine the value or the value of soil erodibility K at various heights along the road Manado - Tomohon. The metode used in this research is the method of stratified random. Analisis soil texture using a pipette. The data is then inserted in the soil texture triangle K values for determining the K value of the land at any altitude. Things are observed is 1). Slopes, 2). land use, 3). Soil texture, and 4). K Value. The data obtained in terms of three grades K arranged in tabular form to determine the value of K dignity and then described descriptively. The results showed that at altitude: 1). 200 m above sea level K value of 0.379; 2). 300 m asl K value of 0.393, 3). 400 m asl value amounted to 0,384 K, 4). 500 m above sea level K value of 0.397, 5). 600 m asl K value of 0.376, 6). 700 m above sea level K value of 0.370, and 7). 800 m asl K value of 0.430. Based on the K value obtained at each altitude or soil erodibility K values are rather high. Keywords: Erodibility Land (K), High Places